2003
DOI: 10.1080/00365590310006354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracorporeal shock‐wave lithotripsy on intrarenal resistive index

Abstract: Patients with renal stones had a temporary increase in RI in the hours following ESWL in both the ipsilateral and contralateral kidneys, which was highest in the region near the stones and lowest in the contralateral kidney. Two weeks later, the RI in both areas had returned to pre-ESWL levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
0
19
1
Order By: Relevance
“…Nazaroglu et al demonstrated that there was no meaningful relationship between the applied energy and increase of vascular RI. 27 In our study, no relationship was found between shock power and vascular RI variations (the difference between vascular RI before and after lithotripsy). Our study found a meaningful relationship between age and vascular RI measured after 1 week.…”
Section: Discussioncontrasting
confidence: 37%
“…Nazaroglu et al demonstrated that there was no meaningful relationship between the applied energy and increase of vascular RI. 27 In our study, no relationship was found between shock power and vascular RI variations (the difference between vascular RI before and after lithotripsy). Our study found a meaningful relationship between age and vascular RI measured after 1 week.…”
Section: Discussioncontrasting
confidence: 37%
“…A transient decrease in the perfusion of treated (and contralateral) kidneys has been reported for up to 24 h after a SWL session [10,11]. These effects were not observed 2 weeks after the SWL session [11].…”
Section: Discussionmentioning
confidence: 88%
“…A transient decrease in the perfusion of treated (and contralateral) kidneys has been reported for up to 24 h after a SWL session [10,11]. These effects were not observed 2 weeks after the SWL session [11]. If we consider reduced urine production as a result of decreased kidney perfusion after SWL, then we can hypothesize that sleeping ipsilaterally can counteract this reduced blood flow by increasing the flow to the dependent kidney and possibly improves stone fragmentation and clearance through improved diuresis.…”
Section: Discussionmentioning
confidence: 98%
“…Almost all radiological studies in the literature have focused on the limitations of radiologic tools to understand SWL-related changes. Among these tools, CDU is easy to apply, cost effective, and has the potential to determine renal function and kidney microcirculation [8,9,[15][16][17]. CDU was recently used as a noninvasive method to estimate renal function and has been used to obtain functional information after SWL sessions.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the radiological tools have been until now used to investigate the interval required between two SWL sessions. Measurement of the renal arterial resistive index (RI) of the kidney is a recently applied successful radiological tool that can reveal the resistance of intrarenal arteries, indirectly demonstrating effective renal blood flow [8][9][10]. Recently, it was shown that shock waves may decrease renal blood flow, which can lead to transient impairments in renal function after SWL [11].…”
Section: Introductionmentioning
confidence: 99%